Der Wert der Reisezeit deutscher Pendler. (17th July 2013) - Obermeyer, Andy; Evangelinos, Christos; Besherz, Andreas
Abstract Travel time savings are usually the most important utility component of transport projects. This paper shows estimation of the value of travel time savings (VTTS) with particular focus on random parameter models. Employing these models commuters' VTTS in the German City Dresden is estimated. Results show that travel time savings of motorised and non‐motorised modes are valued differently, VTTS derived in this study are higher than values currently used in Germany's federal transport infrastructure plan and VTTS are dependent on travel time.